2013
DOI: 10.1002/btpr.1677
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of galanthamine production by leucojum aestivum shoots grown in temporary immersion system

Abstract: The influence of different elicitors (copper sulfate, silver nitrate, salicylic acid and methyl jasmonate), on both the growth and alkaloid production of Leucojum aestivum shoots grown in a temporary immersion system was studied. Seven Amaryllidaceae alkaloids and three protoalkaloids were quantitatively determined by GC-MS analysis in leaves and bulblets, separately. Methyl jasmonate was found to significantly improve the production of galanthamine (GAL) in both leaves and bulblets. The content of GAL release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…radiata); 53,54 the first two methods have been suffering from technical problems, so the in vitro culture technique can be an alternative source of galanthamine. 55 Scholars have carried out many tests about the effectors of in vivo culture in L. aestivum, such as mineral nutrients, 56 carbohydrate sources, 57,58 auxins, 59 cytokinins, 60 ethylene and melatonin, [61][62][63] and physical factors (temperature and medium) on alkaloid synthesis, 64 in which Ptak's team has made a remarkable contribution.In addition, studies on the induction of methyl jasmonate and salicylic acid [65][66][67] and the use of labeling to determine the biotransformation of the precursor 4′-O-methylnorbelladine have also been reported. [68][69][70] L. aestivum in vitro culture has been improving to aid production; the first document about temporary soaking measures in stem segment culture was from Ivanov, and the result showed that the highest production of galanthamine was achieved by soaking at a frequency of 15min at 26°C.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…radiata); 53,54 the first two methods have been suffering from technical problems, so the in vitro culture technique can be an alternative source of galanthamine. 55 Scholars have carried out many tests about the effectors of in vivo culture in L. aestivum, such as mineral nutrients, 56 carbohydrate sources, 57,58 auxins, 59 cytokinins, 60 ethylene and melatonin, [61][62][63] and physical factors (temperature and medium) on alkaloid synthesis, 64 in which Ptak's team has made a remarkable contribution.In addition, studies on the induction of methyl jasmonate and salicylic acid [65][66][67] and the use of labeling to determine the biotransformation of the precursor 4′-O-methylnorbelladine have also been reported. [68][69][70] L. aestivum in vitro culture has been improving to aid production; the first document about temporary soaking measures in stem segment culture was from Ivanov, and the result showed that the highest production of galanthamine was achieved by soaking at a frequency of 15min at 26°C.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…The combination of elicitor (Chitoplant ® ) and TIS (two vessels bioreactor), as a reliable alternative for the genetic modification, increased the cardenolides production 2.2-fold in Digitalis lanata shoots [122], significantly improved galanthamine content in the leaves and bulblets of Leucojum aestivum [126], and stimulated the production of thapsigargin and nortrilobolide in vitro Thapsia garganica shoots [137]. Moreover, the elicitation induced the production and accumulation of phenylpropanoid metabolites in both fresh biomass and culture medium of Aristotelia chilensis [49].…”
Section: Medium Composition and Bioactive Compounds Contentmentioning
confidence: 99%
“…Consequently, alternative approaches have been explored by researchers to ensure its sustainable production ( Pavlov et al, 2007 ; Ferdausi et al, 2019 ). For example, in vitro cultures have been used to effectively produce Gal ( Ivanov et al, 2013 ; Schumann et al, 2013 ; Berkov et al, 2014 ; Saliba et al, 2015 ). In addition, various elicitors have been used to increase secondary metabolite levels ( Jimenez-Garcia et al, 2013 ; Ji et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%